an investigation into linguistic features of statements denoting student learning outcomes of universities in english speaking countries. - Huỳnh Thị Mỹ Hạnh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study aims at finding out the syntactic and semantic features of statements denoting student learning outcomes of universities in English speaking countries for the purpose of implication in learning English and writing student learning outcomes. The data for the study was extracted from ten university websites. 250 samples quoted from student learning outcomes are analyzed such as adjective group, noun group, verb group, adverb group, and. The study was carried out through the adoption of descriptive and qualitative approaches. In terms of syntactic feature, the data was examined in view of clause as message and nominal group in functional grammar. In terms of semantic feature, the data was examined in terms of verb meaning and classified in view of Bloom’s and Revised Taxonomy. The study found that statements in SLOs were structured by the various experiential structures of groups written and cooperated by clausal elements like Classifier, Epithet, Thing in Nominal, and Finite, Event in Verbal group and Modifier plus Head in Adverbial and Adjective group. For beyond clause, function of Theme and Rheme in clause and clause complex was found. In addition to what meaning of verbs was classified clearly in 6 Bloom’s classifications and in 14 sub-categories. It is hoped that the findings of the research will make a certain contribute to learning English, writing and assessing student learning outcomes.